Ricuccio (Yves Montand) walking in the snow - De Santis, Giuseppe, 1917-1997 (Z. Smith Reynolds Library, Wake Forest University, 1956)
The film takes place in a small, isolated town, Vischio, in the Apennine Mountains. The film opens to a snow-covered village as a new family arrives in the village.
Keywords: Apennines (Italy) -- Rural conditions -- Drama; Armendariz, Pedro, 1912-1963; Cefaro, Irene, 1935-; Mangano, Silvana, 1930-1989; Montand, Yves, 1921-1991; Motion picture actors and actresses -- Italy; Motion picture producers and directors -- Italy; Motion pictures -- Italy -- History -- Sources; Stills (motion pictures); Wolf hunting -- Italy -- Drama